2003
DOI: 10.1074/jbc.m303157200
|View full text |Cite
|
Sign up to set email alerts
|

TTF-1, a Homeodomain-containing Transcription Factor, Participates in the Control of Body Fluid Homeostasis by Regulating Angiotensinogen Gene Transcription in the Rat Subfornical Organ

Abstract: In recent years, it has become increasingly evident that angiotensins synthesized in the brain contribute to regulating body fluid homeostasis. Although angiotensinogen, the unique angiotensin precursor, is produced in the brain, the factors that regulate its gene expression remain unknown. We recently found that TTF-1, a homeodomain-containing transcription factor essential for the development of the fetal diencephalon, is postnatally expressed in discrete areas of the hypothalamus. We now report that the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 61 publications
(67 reference statements)
0
27
0
Order By: Relevance
“…We and others have reported that TTF-1 remains expressed in the discrete regions of the postnatal rat brain (15,16). More recently, we showed that TTF-1 is expressed in the subfornical organ where it regulates angiotensinogen synthesis (17).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…We and others have reported that TTF-1 remains expressed in the discrete regions of the postnatal rat brain (15,16). More recently, we showed that TTF-1 is expressed in the subfornical organ where it regulates angiotensinogen synthesis (17).…”
mentioning
confidence: 87%
“…The AS TTF-1 ODN used to disrupt TTF-1 synthesis (5Ј-GAC TCA TCG ACA TGA TTC GGC GTC-3Ј) was directed against the sequence surrounding the first ATG codon of TTF-1 mRNA as reported previously (17,18). As a control, a scrambled (SCR) sequence of identical base composition was used (5Ј-AGT CCT ACT CGG TAC GTA TGC AGC-3Ј).…”
Section: Ttf-1 Regulates Aquaporin-1 Synthesis In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of neuronal TTF1 perturbs expression of genes involved in the control of puberty TTF1 remains expressed after birth not only in hypothalamic neurons but also in ependymoglial cells lining the third ventricle (Lee et al, 2001) and circumventricular organs (Son et al, 2002), precluding the use of conventional gene targeting approaches to identify neuronal versus glial sites of TTF1 action. To circumvent this limitation, we bred mice carrying Ttf1 floxed alleles at the Ttf1 locus (Kusakabe et al, 2006) to transgenic mice in which Cre recombinase is expressed under the control of the synapsin I gene promoter (henceforth referred to as SynCre mice).…”
Section: Estradiol Does Not Transregulate Ttf1 Gene Transcriptionmentioning
confidence: 99%
“…A subset of precursor cells expressing TTF-1/NKX2.1 migrates tangentially from the medial ganglionic eminence of the ventral telencephalon to the developing striatum and to the developing cortical plate (Marìn and Rubenstein, 2001;Anderson et al, 2001). TTF-1/NKX2.1 expression in the adult persists in the hypothalamus and in the subfornical organ, a circumventricular organ of the third ventricle (Lee et al, 2001;Son et al, 2003). TTF-1/NKX2.1 homozygous mutant mice were born dead and lacked completely the thyroid gland and the lung parenchyma, the entire pituitary was missing, and extensive defects were found in the THE INTERNATIONAL JOURNAL OF DEVELOPMENTAL BIOLOGY www.intjdevbiol.com ventral region of the forebrain (Kimura et al, 1996).…”
Section: Introductionmentioning
confidence: 99%